Pemahaman Guru IPA Terhadap Pengajaran Responsif Budaya pada Kurikulum Merdeka Belajar - Abubakar; Yul Ifda Tanjung; Ridwan Abdullah Sani; Budiman Nasution; Yohandri; Festiyed (Postgraduate, University of Mataram, 2024)
This research aims to describe teachers' understanding of Culturally Responsive Teaching (CRT), difficulties to implement it, and its relation to higher order thinking skills through descriptive qualitative method using interview instrument. The research subjects were twenty science teachers from three senior high schools that have implemented Independent Learning Curriculum in Medan City and Deli Serdang Regency in North Sumatera. The results revealed that 70% of teachers have limited understanding and only 30% of the teachers who understand the concept of this learning correctly. The research results also showed that only 20% had ever implemented CRT in their classrooms and 80% had never implemented. This is all due to difficulties. Based on previous research, it shows that CRT make many positive contributions to learning processes and outcomes, improving the learning process and outcomes, improving higher order thinking skills and building student’s character. Therefore, teachers need to understand, be able to design and implement learning model based on CRT to serve diverse students.